Regulation of Malignant Hematopoiesis by Bone Marrow Microenvironment - Asada, Noboru (Frontiers in Oncology, 2018)
Hematopoietic stem cells (HSCs) that give rise to all kinds of hematopoietic lineage cells on various demands throughout life are maintained in a specialized microenvironment called “niche” in the bone marrow (BM). Defining niche cells and unveiling its function have been the subject of intense study, and it is becoming increasingly clear how niche cells regulate HSCs in normal hematopoiesis. Leukemia stem cells (LSCs), which are able to produce leukemic cells and maintain leukemic clones, are assumed to share common features with healthy HSCs. Accumulating evidence suggests that LSCs reside in a specialized BM microenvironment; moreover, LSCs could control and rebuild the microenvironment to enhance their progression and survival. This article discusses the recent advances in our knowledge of the microenvironment supporting malignant hematopoiesis, including LSC niche.